Taxonomy of Crustose Lichens in The Forest of Tahura R. Soeryo, Batu, East Java - Miftahul Jannah; Ludmilla Fitri Untari (Program Studi Biologi, Fakultas Sains dan Teknologi, Universitas Islam Negeri Sunan Ampel Surabaya, 2019)
Lichen is a symbiotic organism consisting of a photobiont (green algae or cyanobacterium) and a mycobiont (fungal). A taxonomic study of the crustose lichens in the forest of TAHURA R. Soeryohad been conducted based on morphological, anatomical, and chemical characters. In this research, we used the method of descriptive exploration to identify the crustose lichens and to study the distribution of the species in the forest of TAHURA R. Soeryo. Twenty species of crustose lichens with one unidentified species and one specimen identified to the group of family are reported. They are Graphina, Graphis, Phaeographis, Pertusaria, Pachyphiale, Phlyctis, Lepraria, Lecanora, Lecania, Cyphellium, and Megalospora. This research also found the new record species of Megalospora kalbii in Java. Crustose lichens are found in the areas with high light intensity of ≥ 1000 lux, average humidity of ≤ 90%, average temperature of18-190C, and at altitudes of ±1640 dpl. Graphina ruiziana could only be found at the altitude of ± 1780 dpl. The identification key to its species and distributions of other species are presented also in the article.